Analyzing the Anomalous Dipole Moment Type Couplings of Heavy Quarks with FCNC Interactions at the CLIC - Tasci, A.T.; Senol, A.; Verep, C. (Hindawi Limited, 2014)
We examine both anomalous magnetic and dipole moment type couplings of a heavy quark via its single production with subsequent dominant standard model decay modes at the compact linear collider (CLIC). The signal and background cross sections are analyzed for heavy quark masses 600 and 700 GeV. We make the analysis to delimitate these couplings as well as to find the attainable integrated luminosities for3σobservation limit.
Keywords: High Energy Physics - Phenomenology; High Energy Physics - Phenomenology (hep-ph); Physics; QC1-999; FOS: Physical sciences; 7. Clean energy